Improving Prison Safety: Breaking the Code of Silence - Kathleen M. Dennehy; Kelly A. Nantel (Washington University Journal of Law & Policy, 2006)
A system permeated by a code of silence reinforces negative behaviors in inmates, ultimately increasing the risk to staff. As the former Massachusetts Secretary of Public Safety, Edward A. Flynn, is keen on saying, “If nothing else, inmates must leave our custody with a belief that there is moral order in their world. If they leave our care and control believing that rules and regulations do not mean what they say they mean, that rules and regulations can be applied arbitrarily or capriciously or for personal interest, then we will fail society, we will fail them, and we will unleash people more dangerous than when they went in.” We know that many offenders go through life believing that rules and laws do not apply to them. If the system in which they are incarcerated lacks integrity and moral order their notions regarding law and order are reinforced. Corrections staff should be the very best people inmates encounter, as we may be the first individuals they are exposed to who do respect rules and laws. We should be role models of positive behavior. If staff members do not follow the rules there is no hope for intervention or for changing inmate behavior in the long term. If staff members are not held accountable we demonstrate that there is no consequence for bad behavior.
Keywords: Correctional personnel; Prison violence; Prisoners; Prison accountability; Prison administration; United States